Genome-Wide Identification and Characterization of the LpSAPK Family Genes in Perennial Ryegrass Highlight LpSAPK9 as an Active Regulator of Drought Stress - Xing, Jing; Zhao, Ruijie; Zhang, Qing; Huang, Xinru; Yin, Tingchao; Zhang, Jing; Xu, Bin (Frontiers in Plant Science, 2022)
SAPK/SnRK2 family genes play crucial roles in plant growth, development, and abiotic stress responses. The objective of this study was to identify and characterize the LpSAPK genes in perennial ryegrass (Lolium perenne L.). The results showed that there are 10 LpSAPKs in perennial ryegrass that could be classified into three groups with similar genic (exon–intron) structures to their orthologous genes in Arabidopsis and other grass species. Ka/Ks analysis suggested that the LpSAPKs and their orthologs were under purifying selection to maintain their conserved function during evolution. Nine out of ten LpSAPKs were localized in the cytoplasm and nucleus with the exception of LpSAPK5 which was only observed in the cytoplasm. Most LpSAPKs were responsive to various abiotic stress and hormonal (ABA, cytokinin, and ethylene) treatments but were downregulated in leaves and upregulated in roots, suggesting that there were unknown cis elements in promoters of these genes or unidentified post-transcriptional mechanism responsible for the tissue-dependent stress-regulated expression of these LpSAPKs. Furthermore, LpSAPK9 was identified as a candidate positive regulator in drought tolerance using a yeast ectopic expression system, and LpSAPK9 showed contrasting expression changes in drought-sensitive and -tolerant ryegrass varieties, suggesting that expression levels of LpSAPK9 were related to ryegrass drought tolerance. These results will facilitate further functional analysis of LpSAPKs for molecular breeding of ryegrass and other related grass species.